Community Engagement in Eradicating Corruption: Evaluating the Effectiveness and Reward Models for Whistleblowers As a Regional Strategy - Suteki Suteki; Abdul Jalil; Aga Natalis; Dewi Rembulan (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2025)
Corruption represents a distinct social phenomenon within Indonesia's legal framework, which is rooted in the principles of a welfare state. Combating corruption requires more than enforcing formal regulations; it involves integrating cultural values, promoting good governance, and fostering active community participation. This study addresses these dimensions by examining the effectiveness of offering rewards to whistleblowers in regional corruption cases, investigating the factors that influence the success of these systems, and developing an optimal model for compensating whistleblowers to strengthen corruption eradication initiatives. The research combines normative legal analysis with sociological insights by employing a socio-legal framework—an approach that examines how law operates within its social context, considering both legal rules and their practical implementation in society. The findings reveal five key factors affecting the efficacy of reward systems: law enforcement, infrastructure, community involvement, cultural attitudes, and regulatory frameworks. The study highlights the importance of developing specific technical guidelines, providing robust protections for whistleblowers, ensuring transparent budget allocation processes, and fostering better coordination among law enforcement agencies. A well-structured reward system has the potential to enhance public trust, increase community participation, and cultivate a sustainable anti-corruption culture. This represents a strategic investment in achieving transparent, clean, and accountable governance in Indonesia.